The Transmigration of the Javanese Ethnic Group in Bangun Rejo Village, Kutai Kartanegara (1980–1983) - Aulia Maghfiroh; Muhammad Azmi; Norhidayat Norhidayat (Yupa: Historical Studies Journal, 2025)
This research explains the background of the transmigration of Javanese tribes to East Kalimantan, namely to Bangun Rejo Village in 1980-1983. This research aims to find out the factors behind their transmigration and the dynamics they faced during the transmigration process. The method used is the historical method, including heuristics, source criticism, interpretation, and historiography, with data in the form of the phenomenon of the Soeharto era transmigration program and population distribution. The results showed that transmigration was a national effort to overcome poverty and develop inland areas as well as equalize the population throughout Indonesia. Transmigrants were given land to cultivate and financial support for one year. The program aims to provide new opportunities for those who want to build a life in developing areas. This research also illustrates the challenges of transmigrants' adaptation and integration with local communities.